A four-scroll chaotic generator based on two nonlinear functions and its telecommunications cryptography application - Karawanich, Khunanon; Kumngern, Montree; Chimnoy, Jirat; Prommee, Pipat (My University, 2022)
This paper describes a new chaotic jerk system based on two different nonlinear functions. The modified signum and rectangular functions are incorporated into the system at different positions. The system can generate double-scroll and new four-scroll chaotic attractors by adjusting only one coefficient (k). The chaotic behaviors of the proposed system are investigated by the Lyapunov spectrum and period distribution of state variable × of the bifurcations. The complexity of the proposed chaotic system is computed by the Kaplan-Yorke dimension of 2.30. The coexisting attractors and basin of attraction are also included to verify the system's dynamic to the initial conditions. The PCB prototype's commercially available OPAMP and passive components are realized to confirm the numerical studies. The experimental results and the numerical results are agreeable in signals and attractors. The chaotic masking method is applied for encrypting the data for secure communication. The efficient encrypted signal can be obtained, and the decrypted data can be correctly received after successful synchronization.
Keywords: 4-scroll attractor; Chaotic system; Cryptography; Jerk model; Nonlinear dynamics